Preparation and Stability of Inorganic Solidified Foam for Preventing Coal Fires - Botao Qin; Yi Lu; Fanglei Li; Yuwei Jia; Chao Zhu; Quanlin Shi (Advances in Materials Science and Engineering)
Inorganic solidified foam (ISF) is a novel material for preventing coal fires. This paper presents the preparation process and working principle of main installations. Besides, aqueous foam with expansion ratio of 28 and 30 min drainage rate of 13% was prepared. Stability of foam fluid was studied in terms of stability coefficient, by varying water-slurry ratio, fly ash replacement ratio of cement, and aqueous foam volume alternatively. Light microscope was utilized to analyze the dynamic change of bubble wall of foam fluid and stability principle was proposed. In order to further enhance the stability of ISF, different dosage of calcium fluoroaluminate was added to ISF specimens whose stability coefficient was tested and change of hydration products was detected by scanning electron microscope (SEM). The outcomes indicated that calcium fluoroaluminate could enhance the stability coefficient of ISF and compact hydration products formed in cell wall of ISF; naturally, the stability principle of ISF was proved right. Based on above-mentioned experimental contents, ISF with stability coefficient of 95% and foam expansion ratio of 5 was prepared, which could sufficiently satisfy field process requirements on plugging air leakage and thermal insulation.